THE PERFORMANCE OF TJILIK RIWUT AIRPORT TAXIS IN THE CITY OF PALANGKA RAYA CITY ACCORDING TO USER - Ricky Rianto; Tarita Aprilani Sitinjak; Revianti Coenraad (Jurusan Pendidikan Teknologi Dan Kejuruan, 2024)
The existence of the Tjilik Riwut airport plays a big role in the development of the Palangka Raya area and its surroundings, especially in providing convenience for domestic passengers who want to visit Palangka Raya City, especially students or tourists who come from outside the island of Kalimantan. The Tjilik Riwut airport taxi is the only airport taxi owned by the Tjilik Riwut airport taxi in the city of Palangka Raya. and it is necessary to know how the performance of the Tjilik Riwut airport taxi in Palangka Raya City according to airport taxi passengers as a consideration for users in determining the mode of transportation. Sampling was carried out by distributing questionnaires with a total of 94 respondents and then analyzed using the Customer Satisfaction Index (CSI) method to determine the level of customer satisfaction with the performance of airport taxis. The results of the CSI analysis on the performance assessment of Tjilik Riwut airport taxis in the city of Palangka Raya show the numbers 54.99 which are included in the category Quite Satisfied